Altoandina: new variety of forage oats for the Andean area in Colombia - Campuzano-Duque, Luis Fernando (2020)
Introduction. The evaluation and selection of new fodder species with appropriate production and quality attributes is a safe and effective strategy to improve the efficiency of milk production systems in Colombia. Objective. To describe the development process and the main characteristics of Altoandina, a new variety of fodder oats. Materials and methods. During the second half of 2016, an agronomic assessment test (PEA) was carried out in four locations in the Altiplano Cundiboyacense subregion and in four locations in the Altiplano of Nariño subregion, in a randomized complete block design, with two genotypes of fodder oats AV25-S and AV25-T and three varieties (Avenar, Cajica, Cayuse). Results. AV25-S and AV25-T showed: tolerance to overturn unlike the three controls that showed a overturn of more than 30%, resistance to leaf and stem rust, and green forage performance of 64.6 and 65.3 t ha-1, respectively, higher than that obtained in Avenar (55.5), Cajica (43.7) and Cayuse (59.1). Conclusion. AV25-T for its tolerance to overturning, resistance to leaf and stem rust and green fodder yield superior to commercial varieties, was registered in the national cultivar system as a new fodder variety called Altoandina, with recommendation for the Cundiboyacense Altiplano and Nariño Altiplano.